PERAN KEPEMIMPINAN DIGITAL DALAM ERA PENDIDIKAN 4.0 ANALISIS KESIAPAN KEPALA SEKOLAH MENGHADAPI TRANSFORMASI DIGITAL - Mogastra Rachmana Nursi; Giatman; Hasan Maksum (IICLS (Indonesian Institute for Corporate Learning and Studies), 2024)
This research analyzes the role of digital leadership in educational transformation in the Education 4.0 era, with a focus on the readiness of school principals in Indonesia. Using a qualitative approach through literature study, the results show that the majority of school principals do not have sufficient competence to face digital challenges, especially in mastering technology, change management and pedagogical innovation. Key barriers include limited infrastructure, resistance to change, and minimal stakeholder collaboration. Strategy recommendations include digital competency training, improving infrastructure, and developing contextual approaches to overcome these challenges. This study emphasizes the importance of digital in creating an innovative and adaptive learning ecosystem, which supports sustainable educational transformation.